2012
DOI: 10.1063/1.4769356
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photochemical HCOOH production from CO2 and water using an inorganic system

Abstract: We have constructed a system that uses solar energy to react CO2 with water to generate formic acid (HCOOH) at an energy conversion efficiency of 0.15%. It consists of an AlGaN/GaN anode photoelectrode and indium (In) cathode that are electrically connected outside of the reactor cell. High energy conversion efficiency is realized due to a high quantum efficiency of 28% at 300 nm, attributable to efficient electron-hole separation in the semiconductor's heterostructure. The efficiency is close to that of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The authors have previously shown that gallium nitride (GaN) photoelectrodes (PEs) can reduce CO 2 using the photoelectrochemical (PEC) system shown in Figure a , and that the heterostructure of the unintentionally doped (uid-) AlGaN (photoabsorption layer)/highly conductive (n + -) GaN on n-GaN substrate enhanced the efficiency of the reduction through a piezoelectric effect. However, AlGaN can absorb only the UV region of solar light, and therefore almost all of the visible light passed through the device without being absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have previously shown that gallium nitride (GaN) photoelectrodes (PEs) can reduce CO 2 using the photoelectrochemical (PEC) system shown in Figure a , and that the heterostructure of the unintentionally doped (uid-) AlGaN (photoabsorption layer)/highly conductive (n + -) GaN on n-GaN substrate enhanced the efficiency of the reduction through a piezoelectric effect. However, AlGaN can absorb only the UV region of solar light, and therefore almost all of the visible light passed through the device without being absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sophisticated techniques can be employed to modify not only surface reaction sites (surface orientation, atomically regulated steps, and facets) but also the bulk properties in a fashion of semiconductor engineering (such as controlling the potential profile in heterostructures). 8,9) -Ga 2 O 3 is a wide-band-gap semiconductor having an indirect band-gap of 4.8 eV. 10,11) The photocatalytic properties of -Ga 2 O 3 have been investigated in a framework of powder-based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, electrical coupling of reactions in a closed system, in which selective water oxidation to extract electrons and selective CO 2 reduction are functionally coupled, is extremely difficult. Few studies on CO 2 photoreduction utilizing water as an electron donor have been reported for semiconductor photocatalysts [5][6][7][8] ; however, some of them were conducted with an external electrical or chemical bias to assist the reaction, and others were active only under ultraviolet light irradiation. While in the case of complex catalysts, other molecules as sacrificial electron donors are required in place of H 2 O to facilitate the reaction.…”
mentioning
confidence: 99%